DETERMINANTS OF INTENTION TO USE ISLAMIC FINTECH DURING COVID-19 PANDEMIC - Hesniati Hesniati; Rico Limgestu (EKUITAS (Jurnal Ekonomi dan Keuangan), 2023)
Islamic fintech Intention has been growing rapidly in Indonesia in rencent years and drawing attention among practitioners, government, and academics. This study intents to investigate determinant of intention to use Islamic Fintech. Fintech has been regarded as a game changer in terms of bringing finances to those who lack access through information technology and the digital financial landscape. Data in this research was acquired using online questionnaires. There were collected from November 2022 to March 2023 and distributed online to survey 396 Islamic Fintech Users. Hypothesis testing in this study used structural equation modeling on partial least square approach the result revealed those variable of effort expectancy, social influence, government support, perceived ease of use, and perceived usefulness were significant and positively influence on intention to use. Moreover, fear of COVID-19 was negatively significant and moderates perceived risk on dependent variable. Limitation of this study only cover Islamic fintech service peer-peer to lending in Indonesia.